Analysis of the Restraint Model for Mental Disorder Clients in Health Care Facilities - Sitti Sulaihah; Siti Khadijah; Darni Darni (Universitas Airlangga, 2019)
Introduction: The reduction or elimination of restraint for psychiatric patients continues to be an area of concern and debate. The lack of accessible alternatives to restraint shows that nurses need to use restraints. The aim of the study was to gain insights from the restraint model used by mental disorder client nurses in health care facilities.Methods: The method used was the identification of interventions in the literature, the identification of the relevant literature by topic and title, obtaining the literature in full-text form and the analysis of the results from the various interventions used in the literature. We systematically searched Scopus, Proquest and Science Direct by including keywords such as ‘restraint models’ and ‘clinical restraint’. The years were limited to 4 (2015-2018).Results: From the 80 potentially relevant articles, 15 met our eligibility criteria with qualitative and quantitative designs; all discussed restraint interventions. The restraint models for mental disorder clients were physical, mechanical and chemical.Conclusion: This study reports on the latest experience that restraint cannot be eliminated from use. Nurses tended to disagree if the restraint method was removed. Restraint with physical, chemical, and mechanical solutions could be tailored to the client's case in health care facilities. The results of this review should be considered when developing interventions aimed at reducing the use of restraint.